Monomer Conversion, Dimensional Stability, and Biaxial Flexural Strength of Flowable Dental Composites Containing Beta-Tricalcium Phosphate and Andrographolide - Panpisut, Piyaphong; Ounprom, Itthi; Pongnumkul, Supawat; Aium-on, Kanyani (Science & Technology Asia, 2022)
The aim of this study was to develop flowable dental composites containing beta-tricalcium phosphate (TCP) and andrographolide (Andro). The effect of these additives on monomer conversion, dimensional stability (mass/volume changes), and biaxial flexural strength was examined. The composites were prepared with a powder to liquid mixing ratio of 1.7:1 (mass ratio). Liquid phase contained light curable methacrylates. Powder phase contained dental glass, TCP (5 or 2.5wt%), and Andro (5 or 2.5wt%). Monomer conversion was assessed using FTIRATR (n=5). Mass and volume changes were assessed using gravimetric studies (n = 3). Biaxial flexural strength was assessed using a mechanical testing frame (n = 6). Fracture surface was assessed using SEM-EDX. The commercial controls were resin-based materials (Z350 and Riva). The highest conversion was observed with Riva (81%). The conversion of composites containing TCP and Andro ( 53% ) was comparable with that of Z350 (51%). The additives reduced monomer conversion of the composites by 10%. Rising level of TCP and Andro showed minimal effect on the conversion. Mass/volume changes of the experimental composites (1.3wt%, 1.7vol%) were higher than that of Z350 (0.4wt%, 0.6vol%). The additives showed minimal effect on mass/volume changes but reduced BFS of the composites from 183 to 137 MPa. Rising level of Andro reduced BFS by 17% whilst rising TCP level showed negligible effect. Fracture surface revealed calcium phosphates precipitated in the composites. In conclusion, the experimental composites containing TCP and Andro showed comparable monomer conversion but lower strength than Z350. The additives reduced monomer conversion and strength of the composites, but their strength was higher than specified in the standard of dental composite.